2007
DOI: 10.1002/ana.21157
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of MAPT H1 haplotype and subhaplotypes in Parkinson's disease

Abstract: Objective-An inversion polymorphism of approximately 900kb on chromosome 17q21, which includes the microtubule-associated protein tau (MAPT) gene defines two haplotype clades, H1 and H2. Several small case-control studies have observed a marginally significant excess of the H1/H1 diplotype among patients with Parkinson's disease (PD), and one reported refining the association to a region spanning exons 1 to 4 of MAPT. We sought to replicate these findings.Methods-We genotyped 1,762 PD patients and 2,010 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 47 publications
8
145
0
1
Order By: Relevance
“…This is probably because of the relatively small size of the sample used for these experiments, as this locus is a well-known PD risk locus among Europeans. 5,7,9,23,65,66 If the same hypothesis as that presented for GAK/DGKQ is applied, five out of the nine tested SNPs would be borderline significant (in the range of 10 À3 ) supporting a role of this locus in the development of PD among the Dutch.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is probably because of the relatively small size of the sample used for these experiments, as this locus is a well-known PD risk locus among Europeans. 5,7,9,23,65,66 If the same hypothesis as that presented for GAK/DGKQ is applied, five out of the nine tested SNPs would be borderline significant (in the range of 10 À3 ) supporting a role of this locus in the development of PD among the Dutch.…”
Section: Discussionmentioning
confidence: 86%
“…9,18 To determine which of the associated alleles in the MAPT locus were present in H1 (previously associated with PD [19][20][21][22][23][24] ) a two-locus haplotype association analysis of rs1981997 and SNPs in the MAPT region was carried out using PLINK. 15 Although we are aware that the sample size of this cohort has a limited power and a GWAS would probably fail to find any associated locus after correcting for 514 799 independent tests, we decided to carry out this analysis to look for specific PD risk loci in the Dutch population.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…209,210 This was recently confirmed by another large study of 1762 PD patients and 2010 control subjects and was found to be consistent across age, gender, and family history. 211 The deleterious haplotype (H1) and the protective haplotype (H2) actually represent groups of subhaplotypes that have formed independently; however, associations with any of these subhaplotypes have so far been inconsistent. 211 The single-nucleotide polymorphisms that define the parent haplotypes of H1 and H2 are in complete linkage disequilibrium with each other (r 2 ϭ 1), indicating that the functional variation could be anywhere within this large 900-kb region and not necessarily within any segment of MAPT.…”
Section: Maptmentioning
confidence: 99%
“…211 The deleterious haplotype (H1) and the protective haplotype (H2) actually represent groups of subhaplotypes that have formed independently; however, associations with any of these subhaplotypes have so far been inconsistent. 211 The single-nucleotide polymorphisms that define the parent haplotypes of H1 and H2 are in complete linkage disequilibrium with each other (r 2 ϭ 1), indicating that the functional variation could be anywhere within this large 900-kb region and not necessarily within any segment of MAPT. Complex permutations of alternative splicing lead to many different isoforms of tau; so if the association with H1 is due to variation that were to upset this delicate balance of isoforms, it may help to explain the variety of different neurodegenerative phenotypes that exhibit tau pathology.…”
Section: Maptmentioning
confidence: 99%
“…clade is involved in pathophysiologic processes probably as a consequence of more various alternative splicing and expression with clear genetic association to Parkinson's disease (Zabetian et al, 2007), progressive supranuclear palsy , argyrophilic grain disease (Fujino et al, 2005), corticobasal degeneration , frontotemporal dementia (Verpillat et al, 2002) and lower regional cerebral gray matter volume in healthy individuals (Canu et al, 2009). Its association to Alzheimer's disease is also supported by many findings (Myers et al, 2007) but there are controversial results too (Caffrey and Wade-Martins, 2012).…”
Section: Research On 17q2131 In Alzheimer's Diseasementioning
confidence: 95%